Use the fact that L{f'}=sF-f(0) to derive the formula for L{cosh at}

1 answer

cosh(at) = d/dt (1/a sinh(at))
sinh(at) = d/dt (1/a cosh(at))
So,

Since L{f(at)} = 1/|a| F(s/a)
L{cosh(at)} = sL{1/a sinh(t)}
= s/a L{sinh(t)}

L{sinh(at)} = sL{1/a cosh(at)}
= s/a L{cosh(at)} - s/a

So,

L{cosh(at)} = s/a (s/a L{cosh(at)} - s/a
L{cosh(at)}(1-s^2/a^2) = -s/a
= (s/a^2)/(s^2/a^2 - 1)
= s/(s^2-a^2)

Better check my algebra in the middle steps. I think I dropped an "a" somewhere, but the final answer is correct. You work this in the same way you do integration by parts twice for trig functions.
Similar Questions
    1. answers icon 2 answers
  1. Please help! I'm really confused on what it is asking.Use the formula for area of a triangle to derive the formula for the area
    1. answers icon 1 answer
  2. Which of the following distinguishes a fact from an opinion? (1 point)A fact can be changed over time. A fact can be proven
    1. answers icon 1 answer
  3. What distinguishes a fact from an opinion?-A fact can be proven true. -A fact can be changed over time. -A fact can be supported
    1. answers icon 9 answers
more similar questions